2020
DOI: 10.1002/ece3.6247
|View full text |Cite
|
Sign up to set email alerts
|

City limits: Heat tolerance is influenced by body size and hydration state in an urban ant community

Abstract: Cities are rapidly expanding, and global warming is intensified in urban environments due to the urban heat island effect. Therefore, urban animals may be particularly susceptible to warming associated with ongoing climate change. We used a comparative and manipulative approach to test three related hypotheses about the determinants of heat tolerance or critical thermal maximum (CTmax) in urban ants—specifically, that (a) body size, (b) hydration status, and (c) chosen microenvironments influence CTmax. We fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 110 publications
(175 reference statements)
1
18
0
Order By: Relevance
“…It is not known whether these size differences are genetically determined, or whether they result from phenotypic plasticity. In contrast, studies in other ant species did not find a significant relationship between thermal tolerance and body size (Foucaud et al, 2013;Johnson & Stahlschmidt, 2020). When Modlmeier, Pamminger, Foitzik, and Scharf (2012) studied plasticity in cold tolerance in the ant Temnothorax nylanderi, they found no correlation between worker size and the ability to recover from a chill-induced coma; they did, however, highlight the importance of acclimation and suggested that cold tolerance was determined more by differences in physiology than by differences in behaviour or worker size.…”
Section: Discussionmentioning
confidence: 89%
“…It is not known whether these size differences are genetically determined, or whether they result from phenotypic plasticity. In contrast, studies in other ant species did not find a significant relationship between thermal tolerance and body size (Foucaud et al, 2013;Johnson & Stahlschmidt, 2020). When Modlmeier, Pamminger, Foitzik, and Scharf (2012) studied plasticity in cold tolerance in the ant Temnothorax nylanderi, they found no correlation between worker size and the ability to recover from a chill-induced coma; they did, however, highlight the importance of acclimation and suggested that cold tolerance was determined more by differences in physiology than by differences in behaviour or worker size.…”
Section: Discussionmentioning
confidence: 89%
“…Based on our findings, increasing summer temperatures in montane systems will likely be associated with a decrease in the relative abundance of larger bodied bees. Body size of insects can have profound effects on their physiologies and thermal heat tolerances [56,57]. Bees have been shown to have species-specific differences in thermal heat tolerances [5860], and some of this variation can be linked to species traits, such as body size.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses conducted at much smaller geographical scales have found little or no phylogenetic signal. For urban ants in California only a moderate phylogenetic signal was detected in CT max for 11 species (Johnson & Stahlschmidt, 2020). Bujan et al (2020b) studied an ant community in the USA across different seasons and found no phylogenetic signal in CT max for six genera active in the winter, 17 genera active in the spring, and 13 genera active in the summer.…”
Section: (D) Evolutionary Historymentioning
confidence: 99%
“…Analyses conducted at much smaller geographical scales have found little or no phylogenetic signal. For urban ants in California only a moderate phylogenetic signal was detected in CT max for 11 species (Johnson & Stahlschmidt, 2020). Bujan et al .…”
Section: Abiotic and Biotic Determinants Of Ant Thermal Limitsmentioning
confidence: 99%